2020
DOI: 10.1186/s12940-020-00648-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal urinary concentrations of organophosphate ester metabolites: associations with gestational weight gain, early life anthropometry, and infant eating behaviors among mothers-infant pairs in Rhode Island

Abstract: Background Organophosphate esters (OPEs)—used as flame retardants and plasticizers—are associated with adverse pregnancy outcomes such as reduced fecundity and live births and increased preterm delivery. OPEs may interfere with growth and metabolism via endocrine-disruption, but few studies have investigated endocrine-related outcomes. The objective of this pilot study (n = 56 mother-infant pairs) was to evaluate associations of OPEs with gestational weight gain (GWG), gestational age at delivery, infant anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…↑D [142] ↔D [376] ↑↓D [445] ↑P [445] ↑D [445] DDT/DDE ↑ [452,[454][455][456][457][458] ↑D [460] ↑D,T [46,49] ↑D [460] ↑D [253,461,[475][476][477][479][480][481][482][483]491,492,739] ↔D [482] ↑A [474] (continued on next page) ↑D [526,534] ↔A [534] ↓A [533] ↑D [527] ↑A [528,[530][531][532] ↓A [533] ↑D [487,488,490,[558][559][560] ↔D [208,487,562,563] ↑C …”
Section: In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…↑D [142] ↔D [376] ↑↓D [445] ↑P [445] ↑D [445] DDT/DDE ↑ [452,[454][455][456][457][458] ↑D [460] ↑D,T [46,49] ↑D [460] ↑D [253,461,[475][476][477][479][480][481][482][483]491,492,739] ↔D [482] ↑A [474] (continued on next page) ↑D [526,534] ↔A [534] ↓A [533] ↑D [527] ↑A [528,[530][531][532] ↓A [533] ↑D [487,488,490,[558][559][560] ↔D [208,487,562,563] ↑C …”
Section: In Vitromentioning
confidence: 99%
“…Maternal urinary concentrations of bis(1,3-dichloro-2-propyl) phosphate (BDCPP) during pregnancy were associated with a greater infant ponderal index at birth [444]. Additionally, a pilot study (n = 56) found a positive association between BDCPP and increasing infant length and weight in males only [445].…”
Section: Human Studiesmentioning
confidence: 99%
“…DPhP and BDCPP) were detected in maternal urine frequently enough for analysis. This is in part due to the analytical method used to quantify OPE metabolites, which was less sensitive for some metabolites relative to recent studies on this topic [ 22 , 55 , 56 ]. While this has limited our ability to examine associations between OPEs and fetal growth, it is worth pointing out that DPhP and BDCPP are two of the most frequently detected OPE metabolites in the general population [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the US-based Pregnancy Infection and Nutrition Study ( n = 349), OPE concentrations in maternal urine were higher (DPhP median = 1.31 ng/mL, BDCPP median = 1.85 ng/mL) compared to the present study and an inverse association between isopropyl-phenyl phenyl phosphate (ip-PPP) and birth weight was observed in females [ 23 ]. However, other recent US-based cohorts have reported null associations between OPE metabolites and fetal growth outcomes [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…DPhP and BDCPP) were detected in maternal urine frequently enough for analysis. This is in part due to the analytical method used to quantify OPE metabolites, which was less sensitive for some metabolites relative to recent studies on this topic (22,55,56). While this has limited our ability to examine associations between OPEs and fetal growth, it is worth pointing out that DPhP and BDCPP are two of the most frequently detected OPE metabolites in the general population (83).…”
Section: Discussionmentioning
confidence: 99%